Mechanisms of platelet activation: Need for new strategies to protect against platelet-mediated atherothrombosis - Jennings, Lisa K. (Thrombosis and Haemostasis, 2009)
Platelets are central mediators of haemostasis at sites of vascular injury, but they also mediate pathologic thrombosis. Activated platelets stimulate thrombus formation in response to rupture of an atherosclerotic plaque or endothelial cell erosion, promoting atherothrombotic disease. They also interact with endothelial cells and leukocytes to promote inflammation, which contributes to atherosclerosis. Multiple pathways contribute to platelet activation, and current oral antiplatelet therapy with aspirin and a P2Y12 adenosine diphosphate (ADP) receptor antagonist target the thromboxane A2 and ADP pathways, respectively. Both can diminish activation by other factors, but the extent of their effects depends upon the agonist, agonist strength, and platelet reactivity status. Although these agents have demonstrated significant clinical benefit, residual morbidity and mortality remain high. Neither agent is effective in inhibiting thrombin, the most potent platelet activator. This lack of comprehensive inhibition of platelet function allows continued thrombus formation and exposes patients to risk for recurrent thrombotic events. Moreover, bleeding risk is a substantial limitation of antiplatelet therapy, because these agents target platelet activation pathways critical for both protective haemostasis and pathologic thrombosis. Novel antiplatelet therapies that provide more complete inhibition of platelet activation without increasing bleeding risk could considerably decrease residual risk for ischemic events. Inhibition of the protease-activated receptor (PAR)-1 platelet activation pathway stimulated by thrombin is a novel, emerging approach to achieve more comprehensive inhibition of platelet activation when used in combination with current oral antiplatelet agents. PAR-1 inhibition is not expected to increase bleeding risk, as this pathway does not interfere with haemostasis.
Keywords: Antiplatelet therapy; haemostasis; inflammation; platelet activation; thrombosis